Identifying the Core Driver for the Islamic Banking Capital Adequacy Regulation - Henry Penikas; Valeriya Stefanenko (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction: COVID-19 pandemic raised the stability challenges for the modern banking systems. As a remedy, the regulators and investors turned their eyes to the Islamic Banking. Many people view it as a full substitute to the dominant conventional banking establishments. We hypothesized that the benefits of the Islamic Banking can be fully enjoyed if and only if it is accompanied with the robust regulatory framework. Such a framework could offer room for the national discretion to define ‘alpha’ parameter within the capital adequacy ratio. The novelty of our paper is the largest collected to date set of alpha value embedded in the Islamic Banking jurisdictions. Purpose: This research paper aims to able to identify the core driver to locally determine the value of alpha. The credit-to-GDP ratio was shown to be such a driver. We demonstrated that the earlier academic research had offered the Vasicek-based theoretical models for the Islamic Banking that had implied right the opposite values of alpha. Methodology: We have eight independent determinants with presenting the alpha values for 11 countries registered in 2007 and in 2016.Those are the four macroeconomic variables. we have collected the input data for the regression model. Findings: The credit-to-GDP ratio was shown to be such a driver. We demonstrated that the earlier academic research had offered the Vasicek-based theoretical models for the Islamic Banking that had implied right the opposite values of alpha. Thus, the usage of the determinant revealed by us could be of help to the central bankers when shaping the framework for Islamic Banking capital adequacy. Paper Type: Research Article